(The Production Of Rolling Oil Lubricant Using Castor Oil And Chitosan Solution) - Alamsyah, Rizal; -, Joelianingsih; Mitha Mala, Dheni (Warta Industri Hasil Pertanian, 2009)
Rolling oil is one kind of the lubricants which is used for metal working especially for cold rolling mill (CRM), roll collant, roll oil and pickle oil.Mostly, lubricat based rolling oil was derived from mineral or synthetic oil where its source has been depleted. Castor oil has some advantages to be employed for lubricants or rolling oil based materials since it has high load wear index lubricity, and viscosity as well as low pour point. This research was aimed at investigating the production of rolling oil using castor oil with oxidation treatment. Chitosan was also used to know its effect on rolling oil characteristics. The method of rolling oil production was designed y adding NaHSO4 as catalyst into castor oil, dehydrating of castor oil at 200 C during three hour, cooling of castor oil at room temperature, dissolving buthylated hydroxy toluene (BHT), dehydrating oil (oxidation) at 100 C during 8 hours, addition of 1 %, 3 % and 5 % of chitosan solution into oil, and dissolving O-fenilfenol into oil with oxidation treatment showed better result in term of acid number, iodine number, viscosity, and density. The best result of experiments was showed for the oxidixed rolling oil with dehydrated treatment with 5 % chitosan aolution which has acid value 1,1 mg KOH/gr oil, iodine number 59,3 gr iod/100 gr oil, saponification value 196,9 mg KOH/g oil, viscisity 180, 6 cps, density 0,97 gr/ml. In coclusion higher chitosan concentration resulted lower acid and saponification value. On the Other hand higher chitosan concentration affected higher iodine number and viscosity.